Representing place in space and time - methodological aspects in modelling the provenance of cultural heritage knowledge - Albers, Laura; Görz, Günther (Provenance of Knowledge. Proceedings, 2018)
Event-based modelling provides obvious advantages for the modelling of provenance information. In particular, the concept of “place” plays an important role; we compare different definitions and their background. Next, we look at the use of “place” in gazetteers, which are important resources for cultural heritage information, and the relation between place names and their temporal dimension. If we use CIDOC CRM for provenance modelling, the question comes up to what extent the concept of “place” as understood in CRM and its extension CRMgeo provide means to enable interoperability. Originating from a consideration of modelling alternatives in CRM ver. 5 (without CRMgeo), we point out the advantages provided by the integration of CRMgeo into CRM ver. 6. Nevertheless, there are still open questions, and we have to find pragmatic solutions in practical applications. Finally, we present the Bavarian Academy project “Corpus of Baroque Ceiling Paintings in Germany” as an example.<br
UnivIS-Import:2019-08-15:Pub.2018.tech.IMMD.lehstu.agdigi.repres